Canonical and Cross-reactive Binding of NK Cell Inhibitory Receptors to HLA-C Allotypes Is Dictated by Peptides Bound to HLA-C - Sim, Malcolm J. W.; Malaker, Stacy A.; Khan, Ayesha; Stowell, Janet M.; Shabanowitz, Jeffrey; Peterson, Mary E.; Rajagopalan, Sumati; Hunt, Donald F.; Altmann, Daniel M.; Long, Eric O.; Boyton, Rosemary J. (Frontiers in Immunology, 2017)
Abstract Background. Human natural killer (NK) cell activity is regulated by a family of killer-cell Ig-like receptors (KIR) that bind human leucocyte antigen (HLA) class I. Combinations of KIR and HLA genotypes are associated with disease, including susceptibility to viral infection and disorders of pregnancy. KIR2DL1 binds HLA-C alleles of group C2 (Lys80). KIR2DL2 and KIR2DL3 bind HLA-C alleles of group C1 (Asn80). However, this model cannot explain HLA-C allelic effects in disease or the impact of HLA-bound peptides. The goal of this study was to determine the extent to which the endogenous HLA-C peptide repertoire can influence the specific binding of inhibitory KIR to HLA-C allotypes. Results. The impact of HLA-C bound peptide on inhibitory KIR binding was investigated taking advantage of the fact that HLA-C*05:01 (HLA-C group 2, C2) and HLA-C*08:02 (HLA-C group 1, C1) have identical sequences apart from the key KIR specificity determining epitope at residues 77 and 80. Endogenous peptides were eluted from HLA-C*05:01 and used to test the peptide dependence of KIR2DL1 and KIR2DL2/3 binding to HLA-C*05:01 and HLA-C*08:02 and subsequent impact on NK cell function. Specific binding of KIR2DL1 to the C2 allotype occurred with the majority of peptides tested. In contrast, KIR2DL2/3 binding to the C1 allotype occurred with only a subset of peptides. Cross-reactive binding of KIR2DL2/3 with the C2 allotype was restricted to even fewer peptides. Unexpectedly, two peptides promoted binding of the C2 allotype-specific KIR2DL1 to the C1 allotype. We showed that presentation of endogenous peptides or HIV Gag peptides by HLA-C can promote KIR cross-reactive binding. Conclusions. KIR2DL2/3 binding to C1 is more peptide selective than that of KIR2DL1 binding to C2, providing an explanation for KIR2DL3–C1 interactions appearing weaker than KIR2DL1–C2. In addition, cross-reactive binding of KIR is characterized by even higher peptide selectivity. We demonstrate a hierarchy of functional peptide selectivity of KIR–HLA-C interactions with relevance to NK cell biology and human disease associations. This selective peptide sequence-driven binding of KIR provides a potential mechanism for pathogen as well as self-peptide to modulate NK cell activation through altering levels of inhibition. Joint Corresponding Senior Authors.Email:eLong@nih.gov, r.boyton@imperial.ac.uk